European energy industry business strategies - Midttun, Atle, 1952- (Elsevier global energy policy and economics series., 2001)
Since the European Union's de-regulation policy for electricity and energy suppliers was implemented, new strategic configurations have emerged. Traditional restraints of geographical limitations on energy companies have been partly removed: the diversity at national regulatory and company level means that the European scene is one of a multiplicity of strategic configurations and developments, whilst also being complex and segmented. This book highlights the strategic and regulatory challenges of European deregulation, with its main focus being on the business strategies within the emerging de-regulated electricity markets; various regulatory implications which are being raised in this new climate are discussed. Some of the central strategic issues facing the electricity industry in its new competitive context are explored and reviewed, with classical themes debated as a prelude to the following empirical investigation of actual business strategies pursued by the electricity and energy industries. The main section of this work consists of 7 national case studies of business strategies which also include one North and one South American case. These were considered important inclusions as the North American companies are large investors in the European market, whilst the European companies invest in the South American market. The final chapter is a comparison and summary of the national patterns of market structures, business strategies and regulatory styles with a brief look at some challenges to be faced in future.